The forward guidance puzzle - Marco Del Negro; Marc Giannoni; Christina Patterson (Federal Reserve Bank of New York, 2012)
With short-term interest rates at the zero lower bound, forward guidance has become a key tool for central bankers, and yet we know little about its effectiveness. Standard medium-scale DSGE models tend to grossly overestimate the impact of forward guidance on the macroeconomy - a phenomenon we call the forward guidance puzzle. We explain why this is the case and describe one approach to addressing this issue.
Keywords: C53; C54; E52; 330; forward guidance; DSGE models